Antiproliferative effects of zerumbone-hydroxypropyl-ß-cyclodextrin inclusion complex on HepG2 liver cancer cells in vitro - Muhammad Nadzri, Nabilah (2013)
Zingiber zerumbet Smith locally known as ‘lempoyang’ or wild ginger belongs to the Zingiberaceae family. Previous investigations on Z. zerumbet proved that it contained a bioactive compound, zerumbone (ZER), a crystalline sesquiterpene possessing suppressive effect in cancers. The purpose of encapsulating ZER with hydroxylpropyl-β-cyclodextrin (HPβCD) is to modify ZER’s solubility and pharmacokinetic properties making it less harmful to the human body. The objective of this study is to investigate antiproliferative activities of ZER-HPβCD inclusion complex towards HepG2 liver cancer cells. The MTT assay showed that the inclusion complex is cytotoxic towards HepG2 cells with an IC50 of 11.43 μg/ml. Morphological evaluation showed structural changes associated with apoptosis including membrane blebbing, cell shrinkage and chromatin condensation. HepG2 cells treated with the inclusion complex further resulted in cell cycle arrest at G2/M phase with increments of apoptotic cells. Further investigations showed the release of cytochrome c and loss of mitochondrial membrane potential, proving mitochondrial dysfunction upon the ZER-HPβCD treatment as well as modulating pro-apoptotic and anti-apototic Bcl-2 family members with no significant change of p53. The activated Bax will be translocated to the mitochondria, which activates the transformation of mitochondrial function and release of cytochrome c. Upregulation of caspase 3/7, caspase 9 and caspase 8 were also detected with the depletion of BID cleaved by caspase 8 proving that both extrinsic and instrinsic pathway were involved upon ZER-HPβCD induction. Collectively, these results demonstrate that the highly soluble inclusion complex of ZER with HPβCD induce apoptosis programmed cell death in HepG2 cells and can be extrapolated to postulate that caspase 8’s activation is indirectly involved as an interconnection between the extrinsic and intrinsic pathway. Further investigations to this complex are needed to substantiate its use as an anticancer against hepatocellular carcinoma in humans.